Shade-based control of Imperata cylindrica: tree fallows and cover crops - Macdicken, K. G.; Hairiah, K.; Otsamo, A.; Duguma, B.; Majid, N. M. (Springer, 1997)
Imperata is shade-intolerant, although little is known of the relative roles of competition for light, water and nutrients in suppressing its growth. Shading of Imperata results in reduced carbohydrate storage, reduced rhizome and tuber-bulb production, reduced shoot dry weight, increased susceptibility to competition, increased susceptibility to herbicides and decreased vigor/regeneration. Herbaceous cover crops in the genera Calapogonium, Crotoleria, Mucuna and Pueraria have been shown to effectively suppress Imperata growth and can be used to prevent and in some cases eradicate Imperata. Tree fallows with fast-growing species such as Sesbania sesban, Acacia nilotica and Leucaena leucocephala can improve soil physical and chemical properties and suppress weed growth. Forest plantations have been successfully used, particularly with the use of moderate to high tillage, weeding and fertilizer inputs to suppress Imperata growth. These plantations produce marketable wood and reclaim the site for other uses. Additional research is needed to evaluate the specific nature of competition and allelopathic effects from Imperata. Continued evaluation of tree species and provenances for Imperata suppression, forms of tillage after woody fallow crops and the constraints to adoption of cover crops and trees as Imperata control measures are also needed.